The Supplementation of Virgin Coconut Oil (VCO) in The Ration To Increase Carcass Weight and Decrease Duck Meat Cholesterol - Ni Wayan Siti; I Made Mudita (Faculty of Animal Science Universitas Brawijaya, 2009)
An experiment was carried out at Kediri, Tabanan Regency and Animal Nutrition Laboratory to study the effect of the supplementation VCO in the ration to increase carcass weight and decrease duck meat cholesterol. The experiment used a completely randomized design (CRD) with five treatments and four replicates. Each of the replicate used five male Balinese ducks with the same weight. The five treatments were diets without VCO as a control (A), ration with 1% VCO (B), ration with 2% VCO (C), ration with 3% VCO (D) and ration with 4% VCO (E) respectively. Ration and water offered ad libitum. The variables measured were carcass weight, physical carcass composition and meat cholesterol. The result of this experiment showed that the carcass weight, the carcass percentage, the percentage of carcass meat in the B, C, D and E treatments were not significantly (P>0.05) higher than the control, so the percentage of fat carcass subcutan (including skin) and carcass bone percentage were not significantly (P>0.05) lower than the control. Triglyceride in treatment 3% VCO in diets (D) was significantly (P<0.05) higher than treatments B, C and E, but the HDL content in B, C, D and E the treatments were not significantly (P>0.05) higher than the control. The total cholesterol content and LDL in those four treatments were not significantly (P>0.05) lower than the control. From the result of this experiment can be concluded that the supplementation of 1-4% VCO in the ration has not increased to the carcass weight and decreased the duck meat cholesterol. Â Keywords : VCO, duck, carcass weight, and Â meat cholesterol